The larvae of Rhopalopsole vespertilio Chen & Du (Plecoptera: Leuctridae), with biological notes on sympatric Nemoura nankinensis Wu (Plecoptera: Nemouridae) - Chen, Zhi-Teng (Zootaxa, 2020)
At least 56 species of the leuctrid genus Rhopalopsole Klapálek, 1912 are recorded from China. Only the larvae of R. hamata Yang & Yang, 1995 has been previously associated with adults. The larvae of R. vespertilio Chen & Du, 2017 are described for the first time based on specimens from Jurong City, Jiangsu Province of southeastern China. Brief biological notes are provided for R. vespertilio and the sympatric Nemoura nankinensis Wu, 1926.